2021
DOI: 10.1002/hbm.25708
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent theta burst stimulation over the parietal cortex has a significant neural effect on working memory

Abstract: The crucial role of the parietal cortex in working memory (WM) storage has been identified by fMRI studies. However, it remains unknown whether repeated parietal intermittent theta‐burst stimulation (iTBS) can improve WM. In this within‐subject randomized controlled study, under the guidance of fMRI‐identified parietal activation in the left hemisphere, 22 healthy adults received real and sham iTBS sessions (five consecutive days, 600 pulses per day for each session) with an interval of 9 months between the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…CDA analysis was performed following the method of our previous study (Deng et al, 2022). Briefly, we focused our analysis on the delay period (early window: 300-900 ms and late window: 1300-1900 ms) of the preprocessed EEG data on parieto-occipital electrodes (PO3/4, PO5/6, PO7/8) after baseline correction using À1200 to À200 ms prior to the appearance of the memory array.…”
Section: Eeg Data Acquisition and Processingmentioning
confidence: 99%
“…CDA analysis was performed following the method of our previous study (Deng et al, 2022). Briefly, we focused our analysis on the delay period (early window: 300-900 ms and late window: 1300-1900 ms) of the preprocessed EEG data on parieto-occipital electrodes (PO3/4, PO5/6, PO7/8) after baseline correction using À1200 to À200 ms prior to the appearance of the memory array.…”
Section: Eeg Data Acquisition and Processingmentioning
confidence: 99%
“…Repetitive transcranial magnetic stimulation (rTMS) is among the most widely used NIBS techniques adopted in both basic neuroscience research and clinical applications, especially in neuropsychological and neuropsychiatric disorders (Machii, Cohen et al 2006, Ridding and Rothwell 2007, Bakker, Shahab et al 2015, Somaa, de Graaf et al 2022). An increasing number of studies have shown that rTMS can induce neuroplasticity across brain regions, systems, and timescales (Song, Chang et al 2019, Shang, Chang et al 2020, Feng, Deng et al 2022, Fitzsimmons, Oostra et al 2023, Deng, Chen et al 2024), through the long-term potentiation/depression (LTP/LTD) of excitatory synaptic transmission (Esser, Huber et al 2006, Hoogendam, Ramakers et al 2010). Conventional high-frequency rTMS (HF-rTMS >5 Hz) over the left dorsolateral prefrontal cortex (L-DLPFC) can increase executive control functions such as working memory and is a widely adopted treatment protocol for psychiatry disorders such as major depression disorder (MDD) (Avery, Holtzheimer III et al 2006, Teng, Guo et al 2017) and substance use disorders (SUD) (Gorelick, Zangen et al 2014, Coles, Kozak et al 2018).…”
Section: Introductionmentioning
confidence: 99%